First Characterization of a Hafnia Phage Reveals Extraordinarily Large Burst Size and Unusual Plaque Polymorphism - Pan, Lingting; Li, Dengfeng; Sun, Zhitong; Lin, Wei; Hong, Binxin; Qin, Weinan; Xu, Lihua; Liu, Wencai; Zhou, Qin; Wang, Fei; Cai, Ruqian; Qian, Minhua; et al. (Frontiers in Microbiology, 2022)
A unique lytic phage infecting Hafnia paralvei was isolated and identified. Hafnia phage Ca belongs to family Autographiviridae, possessing an icosahedral head with a diameter of 55 nm and a short noncontractile tail. Unusually, the burst size of Hafnia phage Ca of 10,292 ± 1,097 plaque-forming units (PFUs)/cell is much larger than other dsDNA phages reported before. Compared to the genome of the related phage, Hafnia phage Ca genome contains extra genes including DNA mimic ocr, dGTP triphosphohydrolase inhibitor, endonuclease, endonuclease VII and HNH homing endonuclease gene. Extraordinary, the phage developed different sizes of plaques when a single plaque was picked out and inoculated on a double-layer Luria broth agar plate with its host. Furthermore, variable packaging tightness of tail of Hafnia phage Ca, presenting dot-like, bun-like, table tennis racket handle-like or ponytail-like shape, were observed (tail length: 4.35~45.92 nm). Although the complete genome of Hafnia phage Ca is 40,286 bp, incomplete genome with a deletion of a 397 bp fragment, containing one ORF predicted as HNH homing endonuclease gene (HEG), was also found by high throughput sequencing. Most of the genome of the virus particles in large plaques is complete (> 98%), while most of the genome of the virus particles in small plaques is incomplete (> 98%), and the abundance of both of them in medium sized plaques is similar (complete, 40%; incomplete, 60%). In an experiment to see if the phage could be protective to brocade carps intramuscularly injected with H. paralvei LY-23 and phage Ca, the protection rate of Hafnia phage Ca to brocade carp (Cyprinus aka Koi) against H. paralvei was 33.38% (0.01